Pre-service and in-service teachers' professional vision depending on the video perspective—What teacher gaze and verbal reports can tell us - Wyss, Corinne; Bäuerlein, Kerstin; Mahler, Sara (Frontiers in Education, 2023)
Teachers are involved in complex teaching situations every day; thus, they must understand what to pay attention to in the classroom, how this information is to be interpreted, and which teaching decisions become necessary as a result. In educational research, these competencies are known as 'professional vision'. The purpose of this exploratory study was to examine the professional vision of pre-service teachers (PTs) and in-service teachers (ITs) by investigating whether the groups differ in what they notice and how they reason about videotaped classroom events; whether the perspective of the video viewed influences their noticing and reasoning; and to what extent their gaze behavior differs from their verbal statements. Thirty-one PTs and twenty ITs watched a video clip of authentic teaching, shot from different perspectives, and their visual focus of attention was recorded using a remote eye-tracker. Subsequently, participants reported in an interview what they had noticed. The triangulated data show that the gaze behavior of the PTs and ITs did not differ, but the content of their verbal statements did. Depending on the video perspective, participants focused on different subjects, but this difference was not reflected in the verbal data. Thus, the gaze behavior and verbal statements are not consistent. The findings indicate that considering multiple sources and types of data is beneficial to explore professional vision and that further research is needed to understand the concept in depth.